The Effect of Continuous Training for Public Employees on the Quality of Public Service: A Case Study of El Oued University Teachers - Mohammed CHOUCHANI ABIDI (Université of Eloued, 2025)
The effectiveness of public institutions, especially those operating in the higher education sector, depends heavily on the efficiency and resilience of their staff in a time of profound global change. This study explores the impact of continuous training for public sector employees on improving the quality of public service, with a focus on the case study of El Oued University teachers. The main objective is to assess the impact of continuous training programmes on improving performance within higher education institutions. To achieve this, the study examines the basics of effective training, digitisation, pedagogical accompaniment cell, English language teaching and Abroad-Level Improvement Programmes. It also investigates their role in supporting academic excellence and strengthening distinguished academic achievement, thus developing the scientific and pedagogical performance of the university as a whole. This research seeks to bridge the knowledge gap regarding the impact of continuous and structured training programmes on the provision of quality public service in higher education. The research employed a descriptive and analytical method, collecting data through structured questionnaires, a review of official regulations and records from the University's General Secretariat, and secondary sources like scholarly references, articles and books. This triangulation ensured the findings were reliable and comprehensive. The findings reveal that continuous training significantly contributes to improving the overall quality of the public service as well as the university's scientific and pedagogical effectiveness, reflected in more efficient teaching, distinguished scientific production, and enhanced institutional standing at both the national and international levels. In conclusion, continuous training represents a strategic lever to maintain innovation and ensure quality in the provision of public service at El Oued University. The study's findings support the need for comprehensive, evidence-based strategies to institutionalise and expand training initiatives within Algeria's higher education system.
The study concludes that continuous training is a strategic lever for innovation. It calls for the institutionalization of these initiatives within the Algerian higher education system, moving from isolated efforts to a comprehensive, evidence-based national strategy.
Keywords: Continuous Training; El Oued University; Higher Education; Public Service Quality; Teacher Professional Development.